2020
DOI: 10.3390/w12061689
|View full text |Cite
|
Sign up to set email alerts
|

Does the Process of Passive Forest Restoration Affect the Hydrophysical Attributes of the Soil Superficial Horizon?

Abstract: There has been an increase in the area of secondary tropical forests in recent years due to forest restoration in degraded areas. Recent analyses suggest that the success of passive forest restoration is highly uncertain and needs to be better understood. This study aimed to investigate the behavior of saturated hydraulic conductivity (Ks) and some hydrophysical soil attributes between agricultural land uses, restored forests, and a degraded forest fragment. The areas evaluated are located in the municipality … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
6

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 72 publications
0
14
0
6
Order By: Relevance
“…Zwartendijk et al [53] point out that the full hydrological recovery of tropical degraded sites with a natural regeneration process, may take several decades. However, K s does not always increase during natural regeneration, in some cases the evolution of K s and hydrological functions can be a relatively slow process [15,50,54,55]. Pereira et al [15] showed for the Atlantic forest biome that after 42 years the natural regenerated forest still had similar K s values as the sugarcane site [15].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Zwartendijk et al [53] point out that the full hydrological recovery of tropical degraded sites with a natural regeneration process, may take several decades. However, K s does not always increase during natural regeneration, in some cases the evolution of K s and hydrological functions can be a relatively slow process [15,50,54,55]. Pereira et al [15] showed for the Atlantic forest biome that after 42 years the natural regenerated forest still had similar K s values as the sugarcane site [15].…”
Section: Discussionmentioning
confidence: 99%
“…However, K s does not always increase during natural regeneration, in some cases the evolution of K s and hydrological functions can be a relatively slow process [15,50,54,55]. Pereira et al [15] showed for the Atlantic forest biome that after 42 years the natural regenerated forest still had similar K s values as the sugarcane site [15]. They attributed the results to the legacy effect of intense land degradation before forest regrowth.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although scientific literature has repeatedly highlighted the fundamental role of physical soil indicators associated with water movement through the soil (e.g. infiltration, Ks, water retention, percolation, soil water content, soil water repellency), they are rarely reported in forests undergoing restoration in tropical ecosystems (Zwartendijk et al 2017; Lozano‐Baez et al 2019; Mendes et al 2019; Pereira et al 2020). Few studies (23%) directly measured hydrological processes, such as erosion, runoff, and infiltration.…”
Section: Discussionmentioning
confidence: 99%